Effect of Stomatal Morphology on Leaf Photosynthetic Induction Under Fluctuating Light in Rice - Xiong, Zhuang; Dun, Zhigang; Wang, Yucheng; Yang, Desheng; Xiong, Dongliang; Cui, Kehui; Peng, Shaobing; Huang, Jianliang (Frontiers in Plant Science, 2022)
Plants are often confronted with light fluctuations from seconds to minutes due to altering sun angles, mutual shading and clouds over under natural conditions, which causes a massive carbon loss and water waste. The effect of stomatal morphology on the response of leaf gas exchange to fluctuating light remains disputable. Here, we investigated the differences in leaf stomatal morphology and photosynthetic induction across twelve rice genotypes after a stepwise increase in light intensity. A negative correlation was observed between stomatal size and density across rice genotypes. Smaller and denser stomata contributed to a faster stomatal response under fluctuating light. Plants with faster stomatal opening also showed faster photosynthetic induction and higher biomass accumulation, but lower intrinsic water use efficiency (iWUE) under fluctuating light. Moreover, stomatal morphology seemed to have little effect on the initial and final stomatal conductance, and there was little correlation between steady- and non-steady-state stomatal conductance among different rice genotypes. These results highlight the important role of stomatal morphology in regulating photosynthetic efficiency and plant growth under fluctuating light conditions. To simultaneously enhance leaf iWUE when improving the photosynthetic efficiency under fluctuating light, it may be necessary to take biochemical processes into account in the future.